The Effect of Anticoagulant in Blood Meal Source on the Aedes aegypti Reproductive Ability in Laboratory - Novyan Lusiyana; Budi Mulyaningsih; Sitti Rahmah Umniyati (Pusat Kedokteran Tropis, 2013)
ABSTRACTIntroduction: Aedes aegypti is one of the major vectors of dengue hemorrhagic fever (DHF) that can be reared in laboratory. Artificial membrane feeding (AMF) assay is used as a simulated host to blood feeding mosquitoes in laboratory.Objectives: The purpose of this study are to investigate the effect of heater and the most widely used anticoagulant of K3EDTA, heparin and sodium citrate on blood feeding sucsses, feeding rate, fecundity, hatchability, preadult development and survival rate of Aedes Aegypti colonies maintained by AMF system compared to direct human feeding.Methods: The system consisted of AMF with parafilm membrane which are warmed and not warmed by a waterbath. Human blood samples were used to feed Aedes aegypti using AMF. The number of eggs were counted seven days after feeding after mosquitoes laid the eggs. Every eggs were hatched in a 500 mL of rearing glass to evaluate the hatchability and preadult development. Survival rate is evaluated after blood feeding until 30 days. Data was analyzed using one-way ANOVA and paired t-tests and a p value <0.05 considered as significantly difference.Results: Blood feeding success of Aedes aegypti was not significantly differ when offered blood meal using anticoagulant heparin with heater (82.22%) compare to that of control groups (81.67%) (p=0.917). There was a significant difference in feeding rate (p=0.000), fecundity (p=0.000), hatchability (p=0.000) between groups. All results were higher in heparin than K3EDTA and sodium citrate, but in pre adult development and survival rate K3EDTA showed better result than that of control, heparin and sodium citrate groups. So this anticoagulant was acceptable for maintenance of laboratory colonies of Aedes aegypti.Conclusion: We conclude that heater can increase the blood feeding sucsses. The K3EDTA, heparin and sodium citrate can affect the feeding rate, fecundity, hatchability, and preadult development, but do not affect survival rate. Heparin can be used for routine colonization of laboratory strain of Aedes aegypti with AMF assay.Keywords: Anticoagulants, artificial membrane feeding, reproductive ability, survival rate